Facial Cartilaginous Reconstruction—A Historical Perspective, State-of-the-Art, and Future Directions - Jessop, Zita M.; Hague, Adam; Dobbs, Thomas D.; Stewart, Kenneth J.; Whitaker, Iain S. (Frontiers in Surgery, 2021)
Importance: Reconstruction of facial deformity poses a significant surgical challenge due to the psychological, functional and aesthetic importance of this anatomical area. There is a need to provide not only an excellent colour and contour match for skin defects, but also a durable cartilaginous structural replacement for nasal or auricular defects. The purpose of this review is to describe the history of, and state-of-the-art techniques within, facial cartilaginous surgery, whilst highlighting recent advances and future directions for this continually advancing specialty. Observations: Limitations of synthetic implants for nasal and auricular reconstruction, such as silicone and porous polyethylene, have meant that autologous cartilage tissue for such cases remains the current gold standard. Similarly, tissue engineering approaches using unrelated cells and synthetic scaffolds have shown limited in vivo success. There is increasing recognition that both the intrinsic and extrinsic microenvironment are important for tissue engineering and synthetic scaffolds fail to provide the necessary cues for cartilage matrix secretion. Conclusions and Relevance: We discuss the first-in-man studies in the context of biomimetic and developmental approaches to engineering durable cartilage for clinical translation. Implementation of engineered autologous tissue into clinical practice could eliminate donor site morbidity and represent the next phase of the facial reconstruction evolution.